Zagłada miasta. Warszawa w Pianiście Romana Polańskiego - Jazdon, Mikołaj (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
This article is an analysis of Roman Polanski’ The Pianist, focused on presenting how the city space in this film, both its exteriors and interiors, makes it a story of Warsaw during the Second World War. The gradual destruction of the city is presented in two supplementary fashions. On the one hand, there is as a quasi-documentary reconstruction of the past based on literary (Władysław Szpilman’s diary) and visual (archive photographs and films) material, while on the other, there is a symbolic narration, where particular places and events bear hidden meanings. Next to Chopin and his music, the piano, interiors and city walls, the most meaningful symbol in the film is a monument of Jesus Christ carrying the cross, a statue standing in front of The Church of the Holy Cross in Warsaw, a motif that appears in the second shot of the Pianist and returns three more times during the film.

Autor artykułu, analizując Pianistę Romana Polańskiego, zwraca uwagę na sposób ukazania w tym filmie przestrzeni miasta, tak jakby Warszawa były drugim, obok Władysława Szpilmana, głównym bohaterem filmu. Stopniowe unicestwianie miasta zaprezentowane zostało w obrazie Polańskiego na dwa sposoby: jako oparta na materialne literackim (wspomnienia Szpilmana) i wizualnym (dokumentalne filmy i fotografie z czasów II wojny światowej) rekonstrukcja wyglądu miasta oraz na sposób symboliczny, nadający poszczególnym miejscom i wydarzeniom dodatkową, ukrytą wymowę. Najbardziej brzemienna w znaczenia, obok muzyki Szopena, fortepianu, wnętrz i murów miasta, okazuje się - pokazana już w drugim ujęciu filmu - figura Chrystusa dźwigającego krzyż sprzed kościoła Świętego Krzyża w Warszawie, której motyw powraca w filmie jeszcze trzykrotnie.
The Annihilation of a City. Warsaw in Roman Polanski's The Pianist
Keywords: Warsaw; World War II; ghetto; Holocaust; film space; documentary; archive materials; symbol; Chopin; Jesus Christ; Władysław Szpilman; Roman Polański; Warszawa; II wojna światowa; getto; przestrzeń w filmie; dokument; archiwalia filmowe